PENGGUNAAN MEDIA PEMBELAJARAN KONKRET PAPERLING UNTUK MENINGKATKAN PARTISIPASI AKTIF SISWA KELAS IV SD - Satrio Lesanpuro; Iman Adelia, Shafira; Sri Utami; Filia Prima Artharina; Ri’ah Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Active student participation is an important indicator of successful learning in elementary schools. However, observations conducted in Grade IV C of SD Negeri Sarirejo Kartini revealed that several students were still reluctant to express opinions, participate in discussions, and actively engage in classroom activities. This study aimed to analyze the use of the Paperling (Environmental Problems Board) concrete learning media in improving students’ active participation during environmental pollution lessons. The study employed a qualitative descriptive approach. The research subjects were 26 fourth-grade students of SD Negeri Sarirejo Kartini, Semarang. Data were collected through observations, interviews, and documentation. Data validity was ensured through source and technique triangulation, while data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results showed that the use of Paperling media increased students’ active participation during the learning process. Students became more enthusiastic, actively involved in group discussions, more confident in asking and answering questions, and more cooperative in completing learning tasks. Observation results indicated that students’ active participation reached an average percentage of 86.54%, categorized as very good. The highest participation indicator was group collaboration (96.15%), while asking questions obtained 73.08%. In addition, interview findings revealed that students found the learning activities more engaging and easier to understand because the media provided concrete learning experiences related to everyday environmental issues. Therefore, Paperling concrete learning media can be considered an effective alternative to enhance active student participation in elementary school learning.